2021
DOI: 10.1002/adtp.202100032
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Prospects of Regulatory Functions Mediated by Nitric Oxide on Immunity and Immunotherapy

Abstract: Nitric oxide (NO), as a crucial signaling biomolecule, is closely involved in the cardiovascular, immune, and central nervous system. NO not only participates in the proliferation, differentiation, and activation of immune cells but also regulates the secretion and function of immune-related cytokines. Meanwhile, NO plays an important role in regulating diversified pathological processes, such as cancer, autoimmune disease, pathogenic infection, and so on. Therefore, the intensive immunological study of NO has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 253 publications
(243 reference statements)
0
9
0
Order By: Relevance
“…Clearly, the concentration of .NO, the stability, the triggering signals for its synthesis, the cells involved and its source, its intracellular and extracellular effects, etc., play major roles on the outcome manifested by the various T cell subsets. Several reports in the literature have discussed the roles of iNOS and .NO in T cell differentiation in the thymus and the periphery, its role in the regulation of CD4 and CD8 T cells, Th1, Th2, and Th17 and immunity to infections, cancer and autoimmune diseases [5,[121][122][123][124].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Clearly, the concentration of .NO, the stability, the triggering signals for its synthesis, the cells involved and its source, its intracellular and extracellular effects, etc., play major roles on the outcome manifested by the various T cell subsets. Several reports in the literature have discussed the roles of iNOS and .NO in T cell differentiation in the thymus and the periphery, its role in the regulation of CD4 and CD8 T cells, Th1, Th2, and Th17 and immunity to infections, cancer and autoimmune diseases [5,[121][122][123][124].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…These results showed the considerable potential of BMS-SNAP-MOF for NO therapy of cancer. [56] Small 2022, 18, 2107732…”
Section: In Vitro Gsh-responsive No Release and Cytotoxicitymentioning
confidence: 99%
“…Nitric oxide (NO), as a short-lived physiological and pathological messenger, has been reported to regulate vasodilation, cell proliferation, migration and death, and the reversion of drug resistance. Of late, it has been reported that plasma-generated reactive nitrogen species such as NO radical induced ICD in melanoma and pancreatic tumors. , Additionally, NO has also been reported to inhibit immune escape via various mechanisms such as interfering with PD-L1 activation, downregulating HIF-1α, or relieving hypoxia. Hence, it is speculated that NO serves as an all-in-one immunomodulatory agent that can induce ICD and simultaneously dampen the ITME of tumors for self-amplifying immune therapy independent of other immunomodulatory strategies. However, the inherent instability and short lifespan of NO dramatically limited its applications. To this end, many efforts have been devoted to developing NO delivery carriers, but these have many issues such as low NO storage, premature NO release, or insufficient NO leakage. It is still a big challenge to construct a robust nanosystem that possesses abundant NO storage and precisely unleashes NO on demand.…”
Section: Introductionmentioning
confidence: 99%